Genotypic characterization by MLST of Ornithobacterium rhinotracheale from poultry in Peru - Cotaquispe Nalvarte, Rony Yunior (2021)
The aim of this study was the genotyping of Ornithobacterium rhinotracheale. For this, 36 strains were identified by molecular testing and genotyping was performed by Multilocus Sequence Typing (MLST). The tests identified the type sequences: N.T.1, N.T2 and N.T3, different from the NCBI database and 19 different alleles with 229 polymorphic sites. In addition, 32 strains belonged to the common ST1 genotype. The findings identified at least four genotypes in chickens from various regions of Peru.